ROBUST DECLINE CURVE ANALYSIS - Sutawanir Darwis; Budi Nurani Ruchjana; Asep Kurnia Permadi (IndoMS, 2009)
Empirical decline curve analysis of oil production data gives reasonable answer in hyperbolic type curves situations; however the methodology has limitations in fitting real historical production data in present of unusual observations due to the effect of the treatment to the well in order to increase production capacity. The development ofrobust least squares offers new possibilities in better fitting production data using declinecurve analysis by down weighting the unusual observations. This paper proposes a robustleast squares fitting lmRobMM approach to estimate the decline rate of daily production data and compares the results with reservoir simulation results. For case study, we usethe oil production data at TBA Field West Java. The results demonstrated that theapproach is suitable for decline curve fitting and offers a new insight in decline curve analysis in the present of unusual observations.DOI : http://dx.doi.org/10.22342/jims.15.2.50.105-111